1994
DOI: 10.1111/j.1570-7458.1994.tb01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone traps for monitoring the codling moth: effect of dispenser type, field aging of dispenser, pheromone dose and type of trap on male captures

Abstract: The effects of dispenser type, dispenser aging in the field, pheromone dose in the dispenser and trap type on trapping efficiency of codling moth, Cydia pomonella (L.), males were investigated in Israel. An Israeli-manufactured rubber septum was significantly better than the CM Pherocon cap in attracting males to a Pherocon 1C cap trap or an IPS trap. The effect of aging of the dispenser in the field on trapping efficiency was significant in CM Pherocon caps and the Israeli septa. Captures in traps were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…& Schiff. as the septum age increased (2,14,17), whereas others found no relationship between septa age and moth capture (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…& Schiff. as the septum age increased (2,14,17), whereas others found no relationship between septa age and moth capture (15).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their calculations, they reported that a 1-mg lure should provide optimal attraction for codling moth for up to 4 weeks, whereas a 5-mg lure would remain effective for more than 4 months. Yet, Kehat et al (14) showed that both the release rate and the attractiveness of 1-mg lures declined rapidly after 2 weeks in the field. This apparent inconsistency was attributed to the effects of high summer temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…14 In that experiment the higher incidence of mating was at sunlight. The highest amount of pheromone in the glands is coincident with the period of calling behavior as in other moths, [15][16][17][18] as well as the period of male response to pheromone [19][20][21] and is the time of the highest frequency of matings. However, the time of mating differs from that reported by Michereff 22 because, in the field, both synthetic pheromone and virgin females attracted males at 6 and 7 th hour of photophase, respectively, about 6 h after the time found in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, dispensers made of same materials that have different sex pheromone release rates could Scientific RepoRts | 6:21081 | DOI: 10.1038/srep21081 be provided for the two generations. According to previous studies, the sex pheromone release rate of the rubber dispenser is proportional to the loading rate and is inversely proportional to the hang time 4,6 . Thus, for the overwinter generation, a rubber dispenser with a higher loading rate and low replacement frequency, which can provide a wider range of sex pheromone release rates, is suitable.…”
Section: Discussionmentioning
confidence: 94%